Basal cell carcinomas treated with 0.5% 5‐fluorouracil and 10% salicylic acid topical solution. Issue 3 (23rd April 2019) - Diluvio, Laura; Lanna, Caterina; Lozzi, Flavia; Palumbo, Vincenzo; Bianchi, Luca; Campione, Elena
Abstract: Basal cell carcinomas (BCCs) are the most common nonmelanoma skin cancers. Dermoscopy is an indispensable tool to differentiate superficial BCC from other subtypes and between pigmented and not pigmented ones. Although surgery is considered the gold‐standard therapy, new current pharmacological options are available and focus on tumor eradication, increasing cosmetic results and functionality. 5‐fluorouracil (5‐FU) is a cytostatic drug associated with antimetabolite effects and already approved as monotherapy for superficial BCCs treatment. A recent formulation combining of 5‐FU 0.5% with salicylic acid 10% has been indicated for the management of slightly palpable and/or moderately thick hyperkeratotic actinic keratosis of the face, forehead, and balding scalp in immunocompetent adult patients. This formulation has never been used as treatment for superficial BCC. In this article, we reported superficial BCC clinical and dermoscopic outcomes in two patients treated with this new topical agent, to assess its role in treating these lesions and to point out dermoscopy's usefulness in supporting clinical diagnosis and excluding tumor persistence or recurrence.